STUDENTS’ DRIVE FACTORS OF INTEREST TO CHOOSE DARMA AGUNG UNIVERSITY AND SEGMENTATION. - Runggu Besmandala Napitupulu; Laminar Hutabarat; Sarman Sinaga (Jurnal Darma Agung, 2018)
The study aims to find out the main factors that encourage students to choose to study at the University of Darmaa Agung (UDA); To find out the target market for the UDA. Urgency of research is: Additional information for UDA’s management in institutional development; References to similar research in the future; Increased research performance of UDA lecturers. Research respondents were 202 new UDA students. The analysis technique used is Cluster Analysis and Exploratory Factor Analysis. Research findings were: The optimal target market profile is served by UDA, namely: Birthplace outside Medan in North Sumatra province; Origin of a high school outside Medan in North Sumatra; The number of family members is above 5 people; Parents work as farmers; Addressing Parents outside Medan in North Sumatra; Hobbies Sports, especially football. The main factors that encourage students to choose UDA include the popularity of the university, increased skills / expertise, student affairs, and university governance